Establishment of a staging model for Parkinson’s disease in mice: Staging model for Parkinson’s disease - Tian, Yueqin; Xian, Jianhua; Tian, Yuehua; Gao, Xiaoya (Cellular and Molecular Biology, 2023)
The Parkinson’s disease is the second most common neurodegenerative disease with different pathological mechanisms at each stage. To investigate Parkinson’s disease further, this study was proposed to develop a continuous staging mouse model of Parkinson’s disease to reproduce the pathological features of different stages of Parkinson’s disease. We successively treated the mice with MPTP, and assessed the behavioral performance of the mice with the open field test and the rotarod test, and detected the aggregation of α-syn and the expression of TH protein in the substantia nigra of the mice with western blot test and immunofluorescence test. The results showed that the mice injected with MPTP for 3 days had no significant behavioral changes, no significant α-syn aggregation, but reduced TH protein expression and 39.5% loss of dopaminergic neurons in the substantia nigra, similar to the performance in the prodromal phase of Parkinson’s disease. However, the behavior of the mice continuously treated with MPTP for 14 days was significantly altered, with significant α-syn aggregation, significant reduction in TH protein expression, and 58.1% loss of dopaminergic neurons in the substantia nigra, corresponding to the early clinical stage of Parkinson’s disease. In the mice that were exposed to MPTP for 21 days, the motor impairment was more obvious, the α-syn aggregation was more significant, the reduction of TH protein expression was more evident, and the loss of dopaminergic neurons reached 80.5% in the substantia nigra, showing a clinical progression similar to that of Parkinson’s disease. Consequently, this study found that continuous treatment of C57/BL6 mice with MPTP for 3, 14 and 21 days could construct mouse models of prodromal, early clinical and clinical progressive stages of Parkinson’s disease, respectively, providing a promising experimental model foundation for the study of the different stages of Parkinson’s disease.